German Orientalism and its Attention to Quranic Readings - Hussein , Ibrahim (Islamic Sciences Journal, 2023)
The orientalists have great efforts in studying the Islamic and Arab heritage, and the Germans have a special interest in the Holy Qur'an, its history, readings, and drawing. This research is an attempt to show the care of the oriental orientalism of the Qur'anic readings since the beginning of the orientalist movement. The printing of the Holy Quran in Arabic, and the translation of its meanings into German. The research reached important results, including: that most of the reasons and motives behind the Orientalism are religious reasons, economic colonialism reasons, and there are real scientific reasons, but they are very few as compared to other reasons and motives.